Distribution and ecotoxicology of bioavailable metals and As in surface sediments of Paraguaçu estuary, Todos os Santos Bay, Brazil. - Pereira, Taís de S. (2019)
Surface sediments collected in the intertidal zone of Paraguaçu estuary in July, 2013, were analyzed for organic matter, nitrogen, phosphorus, grain size fractions and partial concentrations of 16 metals. The USEPA 3051A method and ICP-OES and CV-AAS techniques were chosen to metal analysis. Pollution indices (EF, Igeo and PIN) and a comparison with sediment quality guidelines (UET, ERL, ERM, TEL and PEL of NOAA) were conducted in order to evaluate the potential metal impacts over the area. Principal Component Analysis (PCA) and Pearson correlation results showed the importance of organic matter content and the fine-grained fraction of sediments on the control of the bioavailable metals distribution. The Paraguaçu estuary already has anthropogenic enrichment relative to the background level, especially for Mn, whose values exceeded almost 30 times the background at one site (Mn: 1197.30 mg kg1 ). However, metal levels are still below the reference values with the exception of Hg at one site (Hg: 0.25 mg kg1 , exceeded TEL and ERL).